Motivational Effects of Methylphenidate are Associated with GABRA2 Variants Conferring Addiction Risk - Duka, Theodora; Dixon, Claire I.; Trick, Leanne; Crombag, Hans S.; King, Sarah L.; Stephens, David N. (Frontiers in Behavioral Neuroscience, 2015)
Background: Variations in the GABRA2 gene, encoding α2 subunits of GABAA receptors, have been associated with risk for addiction to several drugs, but the mechanisms by which variations in non-coding regions of GABRA2 increase risk for addictions are not understood. Mice with deletion of Gabra2 show deficits in the ability of psychostimulants to facilitate responding for conditioned reinforcers, offering a potential explanation. Methods: We report human and mouse studies investigating a potential endophenotype underlying this association. Healthy human volunteers carrying either cocaine-addiction ”risk” or ”protective” GABRA2 SNPs were tested for their subjective responses to methylphenidate, and methylphenidate’s ability to facilitate conditioned reinforcement (CRf) for visual stimuli (CS+) associated with monetary reward. In parallel, methylphenidate’s ability to facilitate responding for a visual CRf was studied in wildtype and α2 knockout (α2-/-) mice. Results: Methylphenidate increased the number of CS+ presentations obtained by human subjects carrying protective, but not risk SNPs. In mice, methylphenidate increased responding for a CS+ in wildtype, but not α2-/- mice. Human subjects carrying protective SNPs felt stimulated, aroused and restless following methylphenidate, while individuals carrying risk SNPs did not. Conclusion: Human risk SNP carriers were insensitive to methylphenidate’s effects on mood or in facilitating CRf. That mice with the gene deletion were also insensitive to methylphenidate’s ability to increase responding for CRf, suggests a potential mechanism whereby low α2-subunit levels increase risk for addictions. Circuits employing GABAA-α2 subunit-containing receptors may protect against risk for addictions.